Spinal Muscular Atrophy: Why do low levels of SMN make motor neurons sick? - Burghes, Arthur H.M. (2009)
Many neurogenetic disorders are caused by the mutation of ubiquitously expressed genes. Spinal muscular atrophy is one such disorder and is caused by loss or mutation of the survival motor neuron 1 gene (SMN1), leading to reduced SMN protein levels and a selective dysfunction of motor neurons. SMN, in collaboration with partner proteins, functions in the assembly of small nuclear ribonucleoproteins (snRNPs), which are important for pre-mRNA splicing. It has also been suggested that SMN might function in the assembly of other RNP complexes. Two hypotheses have been proposed to explain the molecular dysfunction that gives rise to SMA and its specificity to a particular group of neurons. The first hypothesis states that the loss of SMN’s well-known function in snRNP assembly causes an alteration in the splicing of a specific gene (or genes). A second hypothesis proposes that SMN is critical for the transport of mRNA in neurons and disruption of this function results in SMA.